2018
DOI: 10.1007/s10096-018-3362-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of fluoroquinolones, macrolides, and imipenem resistance in Haemophilus influenzae: analysis of the mutations in QRDRs and assessment of the extent of the AcrAB-TolC-mediated resistance

Abstract: The aims of the present study were to characterize the mechanisms of resistance to fluoroquinolones, macrolides, and imipenem in Haemophilus influenzae, to assess the extent of the AcrAB-TolC-mediated resistance, and to define a core genome multilocus sequence typing (cgMLST) scheme for H. influenzae by using whole-genome sequencing. Four amino acid substitutions in GyrA (at Ser84 and Asp88), ParC (at Ser84), and ParE (at Asp420) were found to be closely associated to the MICs. We did not find any amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
18
4
Order By: Relevance
“…We detected >20 different resistance genes in the genomes of the G. anatis isolates in our study, including determinants conferring resistance to aminoglycosides, phenicols, macrolides, sulphonamides, trimethoprim, tetracyclines, penicillins, and quinolones. Although many of these resistance genes have been described previously in Pasteurellaceae obtained from either animals or humans (43,44), we detected various other resistance genes not previously reported in G. anatis or bovine Pasteurellaceae. Moreover, 4 resistance genes have so far never been described in Pasteurellaceae at all, namely aadA23, bla CARB-8 , tet(Y) and qnrD1.…”
Section: Discussioncontrasting
confidence: 51%
“…We detected >20 different resistance genes in the genomes of the G. anatis isolates in our study, including determinants conferring resistance to aminoglycosides, phenicols, macrolides, sulphonamides, trimethoprim, tetracyclines, penicillins, and quinolones. Although many of these resistance genes have been described previously in Pasteurellaceae obtained from either animals or humans (43,44), we detected various other resistance genes not previously reported in G. anatis or bovine Pasteurellaceae. Moreover, 4 resistance genes have so far never been described in Pasteurellaceae at all, namely aadA23, bla CARB-8 , tet(Y) and qnrD1.…”
Section: Discussioncontrasting
confidence: 51%
“…While MIC values have been reported to increase as the number of QRDR mutations increases (1321), only one isolate was found to have two mutations in the present study. The isolate 2017-2 showed reduced susceptibility to all fluoroquinolones except for STFX, a finding supporting the above notion (Table 1).…”
Section: Discussioncontrasting
confidence: 69%
“…Isolate 2014-5 showed a high MIC value (0.5 µg/ml) for not only MXF but also CIP and LVX, although this isolate had no mutations in QRDRs of both GyrA and ParC enzymes (Table 1). A factor presumably involved in this is a drug efflux pump (acrAB) (21–22) or H. influenzae -specific porin (2324), the protein structure of which is similar to that of porin (OmpF); however, solid evidence was not obtained from the present study, and this point remains to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 60%
“…A major weakness in the results from these studies was the low number of ‘resistant’ isolates (Georgiou et al ; Biedenbach and Jones ; Pérez‐Vázquez et al ; Yoshizumi et al ; Li et al ; Puig et al ; Fuursted et al ; Cherkaoui et al ). In addition, there were few H. influenzae isolates with high‐level resistance (MICs for levofloxacin or moxifloxacin of >16 μg ml −1 ) reported (Yoshizumi et al ; Li et al ; Kuo et al ; Shoji et al ; Puig et al ; Fuursted et al ; Cherkaoui et al ). Because of the inclusion of more isolates with high‐level resistance to fluoroquinolones, our study provides statistical evidence of the association of MIC levels and the numbers and positions of QRDR mutations, as well as their correlation with nalidixic acid inhibition zone diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone resistance is often caused by mutations in the quinolone‐resistance determining regions (QRDRs) of two principal target enzymes, DNA gyrase, which is partially encoded by subunit genes, gyrA and gyrB, and DNA topoisomerase IV, encoded by parC and parE . The sequences of several fluoroquinolone‐resistant H. influenzae isolates showed amino acid changes at positions 84 and/or 88 in gyrA and/or at the analogous positions (84, 88) in parC (Georgiou et al ; Pérez‐Vázquez et al ; Yoshizumi et al ; Li et al ; Kuo et al ; Shoji et al ; Puig et al ), some studies reported mutations in parE (Fuursted et al ; Cherkaoui et al ). However, since the majority of resistant H. influenzae isolates previously described in QRDR studies had only reduced susceptibility or few numbers of high‐level resistance to fluoroquinolones, no statistical association could be made between mutations and levels of fluoroquinolone resistance (Georgiou et al ; Pérez‐Vázquez et al ; Yoshizumi et al ; Li et al ; Kuo et al ; Shoji et al ; Puig et al ; Fuursted et al ; Cherkaoui et al ).…”
Section: Introductionmentioning
confidence: 99%